Efektivitas Penggunaan Media Audio-Visual dalam Pembelajaran Pendidikan Agama Kristen di SMA Elpida Noelbaki - Ficthor Soleman Missa; Dominggus U. Dingu; Angelita Meneses (Pusat Riset dan Inovasi Nasional, 2021)
This study aims to analyze the effectiveness of using audio-visual media in teaching Christian Religious Education at Elpida Senior High School Noelbaki. The research was motivated by teachers’ need to develop contextual and engaging teaching methods for the digital-native generation. A quantitative approach with a quasi-experimental design was employed. The research population consisted of all 11th-grade students, with a total sample of 60 students divided into experimental and control groups. The instruments used were a Likert-scale questionnaire and observation sheets measuring student learning activities. Data analysis was conducted using a t-test to determine differences in learning outcomes between the two groups. The results revealed that the use of audio-visual media had a significant effect on improving students’ learning outcomes in Christian Religious Education (t = 4.27; p < 0.05). Moreover, students in the experimental group demonstrated higher motivation and participation during the learning process. Therefore, it can be concluded that audio-visual media is effective in enhancing understanding of faith concepts, emotional engagement, and overall learning attractiveness. The findings imply that teachers should receive continuous training to optimize digital technology as a contextual and relevant medium for Christian education today.